A Comparative Study of Digital Marketing Strategies of HDFC Bank and ICICI Bank with Special Reference to Customer Engagement (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid growth of digital technologies has significantly transformed the banking sector in India, compelling financial institutions to redesign their marketing approaches to remain competitive and customer-centric. This study presents a comparative analysis of the digital marketing strategies adopted by HDFC Bank and ICICI Bank, with particular emphasis on customer engagement practices. Both banks are among the leading private sector banks in the country and have made substantial investments in digital platforms to strengthen their market presence and enhance customer interaction.The research examines various components of digital marketing, including social media outreach, mobile banking applications, personalized email campaigns, content marketing, search engine visibility, and the use of data analytics for targeted communication. The study evaluates how these strategies influence customer awareness, satisfaction, loyalty, and overall engagement. Attention is also given to the user experience offered through digital interfaces, responsiveness on social media channels, and the integration of innovative technologies such as chatbots and AI-driven support systems.Primary and secondary data have been considered to understand customer perceptions and preferences regarding digital communication by both banks. The findings highlight differences in strategic focus, content style, platform utilization, and engagement metrics. While one bank may emphasize technology-driven personalization and automation, the other may ocus more on relationship-oriented communication and brand storytelling.The study concludes that effective digital marketing in the banking sector extends beyond promotional activities and plays a vital role in building trust, transparency, and long-term customer relationships. The comparative insights offered in this research may assist banking professionals, marketing practitioners, and researchers in understanding evolving digital engagement trends and in developing more responsive and customer-focused digital strategies.